2021
DOI: 10.1101/2021.05.19.21257413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global research on syndemics: A meta-knowledge analysis (2001-2020)

Abstract: Syndemics or synergies of cooccurring epidemics are widely studies across health and social sciences in recent years. We conducted a meta-knowledge analysis of articles published between 2001 to 2020 in this growing field of academic scholarship. We found a total of 830 articles authored by 3025 authors, mostly from high-income countries. Publications on syndemics are gradually increasing since 2003, with rapid development in 2013. Each article was cited more than 15 times on average, whereas most (n = 604) ar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…The syndemics theory has enabled scholars to identify particular sub-populations and specific community strata at higher risks for developing/spreading HIV/AIDS, such as gay and bisexual individuals and other men having sex with men (GBMSM), or youth living with HIV (YLWH). Other examples of vulnerable and frail populations include individuals suffering from mental health disorders and other issues (such as depression, binge drinking, (poly-)substance use, street drug use, psychological distress, childhood sexual abuse, intimate partner violence and sexual assault as well as other psychosocial risk factors) or subjects experiencing stigma, a lack of strong social support networks, other psychological burdens, and/or low socio-economic status [1][2][3][4][5][6][7][8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The syndemics theory has enabled scholars to identify particular sub-populations and specific community strata at higher risks for developing/spreading HIV/AIDS, such as gay and bisexual individuals and other men having sex with men (GBMSM), or youth living with HIV (YLWH). Other examples of vulnerable and frail populations include individuals suffering from mental health disorders and other issues (such as depression, binge drinking, (poly-)substance use, street drug use, psychological distress, childhood sexual abuse, intimate partner violence and sexual assault as well as other psychosocial risk factors) or subjects experiencing stigma, a lack of strong social support networks, other psychological burdens, and/or low socio-economic status [1][2][3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…Adopting a bio-psycho-social perspective and, more specifically, a syndemic lens is of paramount importance in devising and designing public health preventative strategies and interventional approaches aimed at improving and enhancing community wellbeing, which results from the complex, non-linear interaction between societal, economic-financial, environmental, cultural, and political variables [8].…”
mentioning
confidence: 99%
“…Syndemic theory has been applied to investigate the clustering and synergistic interactions among communicable and non-communicable diseases among a wide range of populations and contexts using a range of qualitative and quantitative methods that have benefited from rich interdisciplinary contributions from across scholarly disciplines, including anthropology, epidemiology, medical, and social sciences (Hossain et al, 2021). Such methods include: qualitative and mixed-methods assessments to explore underlying structural contexts; community-based participatory research (CBPR) to ensure contextual and cultural relevance; and epidemiology and biomedical evidence to identify mechanisms that link SAVA.…”
Section: Applying Syndemic Theory To Designing Integrated Interventio...mentioning
confidence: 99%
“…One of the syndemic clusters that has received the most attention globally is that of type 2 diabetes (T2D) and depression [9][10][11][12]. However, most of the available evidence comes from high-income countries and, to a lesser extent, from middle-and low-income countries [10,13,14]. From an epidemiological point of view, it has been found that people with T2D have an increased risk of suffering from depression; in turn, depression has an impact on the development and evolution of T2D (bidirectional causality) [15,16].…”
Section: Introductionmentioning
confidence: 99%